2022
DOI: 10.1093/jnci/djac196
|View full text |Cite
|
Sign up to set email alerts
|

Somatic inactivation of breast cancer predisposition genes in tumors associated with pathogenic germline variants

Abstract: Background Breast cancers (BC) that arise in individuals heterozygous for a germline pathogenic variant in a susceptibility gene, such as BRCA1/2, PALB2 and RAD51C, have been shown to exhibit bi-allelic loss in the respective genes, and be associated with triple-negative (TN) BC and distinctive somatic mutational signatures. Tumour sequencing thus presents an orthogonal approach to assess the role of candidate genes in BC development. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Most but not all CHEK2 -associated BCs showed biallelic CHEK2 alteration via LOH, which is in keeping with incomplete rates of LOH seen in prior studies [ 18 , 19 , 29 , 30 ]. A recent study found high rates of CHEK2 LOH in BCs arising in c.1100delC carriers compared to lower rates in other CHEK2 variants [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Most but not all CHEK2 -associated BCs showed biallelic CHEK2 alteration via LOH, which is in keeping with incomplete rates of LOH seen in prior studies [ 18 , 19 , 29 , 30 ]. A recent study found high rates of CHEK2 LOH in BCs arising in c.1100delC carriers compared to lower rates in other CHEK2 variants [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
“…Taken together, our findings and those of others raise consideration that at least some CHEK2 variants may function via haploinsufficiency in driving BC, whereas others (such as c.1100delC) may require bilallelic inactivation. This is in contrast to most other germline BC risk genes, such as BRCA1 / 2, PALB2 , and ATM , PVs of which often show biallelic loss of function in BC [ 29 ]. Alternatively, CHK2 inactivation may also be due to non-genetic mechanisms in cases without LOH, and future studies may help address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…We identified germline CHEK2 variants in 2% of our pediatric/young adult cohort, with no clear discernment toward a particular tumor type. Biallelic alteration of CHEK2 was not identified within this cohort, although biallelic germline or somatic alterations are uncommonly found in adults with CHEK2 -associated cancers [ 54 , 55 , 56 ]. Nonetheless, the variants identified in our study may represent secondary findings amid individuals in a pediatric cancer cohort.…”
Section: Discussionmentioning
confidence: 86%
“…Failure to properly repair the DNA damage leads to tumor cell death. Germline mutations in BRCA1 and BRCA2 are found in roughly 17% of women with epithelial ovarian cancer (EOCs) and 10%–20% of triple negative breast cancers (TNBCs), while somatic mutations are found in approximately 7% of ovarian tumors and 3%–5% of TNBCs 1–6 . Roughly 40%–50% of EOCs have HR deficiencies, while HRD is a frequent occurrence in TNBCs 5–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations in BRCA1 and BRCA2 are found in roughly 17% of women with epithelial ovarian cancer (EOCs) and 10%–20% of triple negative breast cancers (TNBCs), while somatic mutations are found in approximately 7% of ovarian tumors and 3%–5% of TNBCs. 1 , 2 , 3 , 4 , 5 , 6 Roughly 40%–50% of EOCs have HR deficiencies, while HRD is a frequent occurrence in TNBCs. 5 , 6 , 7 , 8 , 9 PARP inhibition of tumors with HRD has led to a dramatic change in the management of EOCs with statistically and clinically significant improvements in outcomes.…”
Section: Introductionmentioning
confidence: 99%